IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH THE SNOWBALL THROWING MODEL ASSISTED BY THE MYSTICAL BOX MEDIA (FUN MYSTERY BOX OF FRACTIONS) - Puspitarini, Aulia; Sukmarani, Dhuta; Rahmawati, Puji; Mir’ati, Khusni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2023)
The aim of this research is to improve the Mathematics learning outcomes of class V A students at SD Negeri Depok 1 Sleman in the odd semester of academic year 2023 - 2024 through learning with the Snowball Throwing Model Assisted by Mystical Box Media. This research is a classroom action research. The subjects of this research were all 28 students in the VA class of SD Negeri Depok 1 Sleman in the odd semester of academic year 2023-2024, consisting of 10 male and 18 female. The object of this research is student learning outcomes. Based on the data analysis result, it can be concluded that student learning outcomes gradually increased from 58.57 (Pre Cycle) to 72.03 in cycle I and to 81.78 in cycle II. Where the percentage of completeness increased from 36% (Pre Cycle) to 50% in cycle I and to 78% in cycle II.